PERAN NILAI WASATHIYAH DALAM MEMBENTUK ETIKA BERAGAMA DI MEDIA SOSIAL - Sultoni Mahendra; Mukh Nursikin (JOURNAL SAINS STUDENT RESEARCH, 2025)
The digital era has brought a significant transformation in the way people practice and express their religious beliefs. Social media has become a new arena for preaching, theological discussions, and the dissemination of religious teachings. However, alongside these positive developments, numerous ethical challenges have emerged, including the spread of hate speech, interfaith polarization, misuse of religious texts for sectarian purposes, and the rise of extremist and intolerant behavior online. These phenomena indicate a moral crisis in digital religiosity that calls for a new ethical paradigm. In this context, the Islamic value of wasatiyah—which emphasizes moderation, balance, and tolerance—plays a crucial role as an ethical foundation for religious conduct in the digital sphere. This study aims to analyze the role of wasatiyah values in shaping ethical religious behavior on social media. Using a qualitative-descriptive approach through library research, this paper examines relevant academic sources such as journals, books, and Islamic literature. The findings reveal that the principles of wasatiyah provide a strategic framework for developing balanced, rational, and civilized religious behavior online. The principle of moderation prevents extremism and provocation, the principle of balance promotes harmony between faith expression and social responsibility, and the principle of tolerance fosters mutual respect amid diversity.Thus, the application of wasatiyah values serves not only as a theological solution but also as an ethical and social framework for addressing the moral crisis in the digital age. These values offer practical guidance for Muslims to cultivate a culture of civility, peace, and inclusivity in online communication, thereby reinforcing Islam’s essence as a religion of rahmatan lil ‘alamin—a mercy for all creation.